An Empirical Study on the Dairy Product Consumers’ Intention to Adopt the Food Traceability’s Technology: Push-Pull-Mooring Model Integrated by D&M ISS Model and TPB With ITM - Lin, Xin; Wu, Run-Ze (Frontiers in Psychology, 2021)
Abstract Against the backdrop of frequent food safety problems, the importance of establishing food traceability systems has become increasingly important and urgent to address the contradiction between consumer information on safe food choices and the proliferation of problematic foods. The purpose of this study is to empirically study the influencing factors of Chinese consumers on the food traceability system in the food safety field (hereinafter referred to as FTS). In this study, multiple models: push factor (information system success model), pull factor (ITM theory), mooring factor (TPB) and switching intention were integrated into the push-pulling-mooring theory (PPM) to form a conceptual PPM comprehensive model framework to study the switching intentions of two-dimensional code traceability technology for Dairy products of Chinese consumers. By collecting the questionnaire survey, 305 valid questionnaires were collected from the consumers of middle and high-end dairy products in China, and the influencing factors of thrust, pull and mooring force were identified. The results showed that 10 of the 11 hypotheses were positive, but the impact of perceived risk on user satisfaction was negative. The important value of this study is to conduct a comprehensive empirical analysis of the key factors influencing consumer choice of traceable safe food through an integrated multi-model framework to help identify ways to establish and improve consumer willingness to use QR code traceable system products, to increase consumer confidence in the use of traceable and safe food choices.